"Condemned to Disappear": Indigenous Genocide in Tierra del Fuego. Issue 1 (2nd January 2022) - Gigoux, Carlos
ABSTRACT: Nation state building, competing sovereign claims, the capitalist drive for land and resources fuelled by international market forces and prevalent racial ideologies can be identified as major structural factors that leads to the dispossession of indigenous lands and in many cases to the physical destruction of indigenous peoples. In this context settler colonial studies continues to work towards a theory of settler colonialism. This article contributes to these debates by examining the genocide of the Selk'nam in Tierra del Fuego through the lens of extinction discourse. It analyses the way that extinction discourse emerged as an explanatory – and exculpatory – narrative for the fast diminishing numbers of the Selk'nam not only among officials and settlers uninterested in their fates, but also among the missionaries engaged in humanitarian efforts to save them. In particular the relationship between negative stereotypes of primitiveness and savagery and the settler process constitute a major point of analytical inquest. This epistemological ambition means that this article is textually based and as such relies on displaying a selection of texts in their original forms contextualised within the history of settler colonialism. It concludes by suggesting that understanding and challenging the role and pervasiveness of social Darwinist discourses on extinction remains a central issue in understanding settler genocides and a challenge for promoting the recognition of indigenous identities and rights.